2008
DOI: 10.1021/jf801465y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Equilibrium Constants of Phytic Acid and Ferric and Ferrous Phytate Derived from Nuclear Magnetic Resonance Spectroscopy

Abstract: Inositol phosphates are metabolically derived organic phosphates (P) that increasingly appear to be an important sink and source of P in the environment. Salts of myo-inositol hexakisdihydrogen phosphate (IHP) or more commonly phytate are the most common inositol phosphates in the environment. IHP resists acidic dephosphorylation and enzymatic dephosphorylation as ferric or ferrous IHP. Mobility of IHP iron complexes is potentially pH and redox responsive, making the time scale and environmental fate and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In addition, the marked lack of the distinctive peak signature associated with the various isomers of inositol hexakisphosphate, even in upland pasture samples, was in contrast to other studies of upland grasslands (Tate and Newman, 1982; Turner et al, 2003b; McDowell and Stewart, 2006; Murphy et al, 2009). The abiotic sorption and stabilization of inositol phosphates in such environments is attributed to their interaction with clay minerals and amorphous Fe and Al oxides (Celi and Barberis, 2007; Heighton et al, 2008). In addition to data presented, which report the low Fe and Al concentrations throughout the system (Table 2), existing soil surveys (Lewis et al, 2003) and detailed particle‐size distribution analysis (Bhadha and Jawitz, 2010) show only minimal clay content (<2.5%) in the uplands.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the marked lack of the distinctive peak signature associated with the various isomers of inositol hexakisphosphate, even in upland pasture samples, was in contrast to other studies of upland grasslands (Tate and Newman, 1982; Turner et al, 2003b; McDowell and Stewart, 2006; Murphy et al, 2009). The abiotic sorption and stabilization of inositol phosphates in such environments is attributed to their interaction with clay minerals and amorphous Fe and Al oxides (Celi and Barberis, 2007; Heighton et al, 2008). In addition to data presented, which report the low Fe and Al concentrations throughout the system (Table 2), existing soil surveys (Lewis et al, 2003) and detailed particle‐size distribution analysis (Bhadha and Jawitz, 2010) show only minimal clay content (<2.5%) in the uplands.…”
Section: Resultsmentioning
confidence: 99%
“…Fe(II) phytates were investigated by many authors [9,20,21,24,47]. Torres et al [24] reported that the highest protonation degree of iron(III) phytate species formed in acidic media is i = 5 and log of the stability constant …”
Section: Iron(iii) Solution Equilibriamentioning
confidence: 99%
“…Among a number of artificially produced as well as in the nature occurring ligands with high affinity to iron ions, inositol hexaphosphate (IP6) possess a specific role. Phytic acid, myo-inositol 1,2,3,4,5,6 hexakis (dihydrogen phosphate) and its salts (phytates) are synthetized in terrestrial ecosystems by plants, and form the dominant class of organic phosphorus [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that soil humic material is capable of forming micelles that can provide protection to labile moieties (Sutton & Sposito, 2005). Formation of micelles is unlikely due to the Beer Lambert behavior seen in all HS in this study (Table 2) but other forms of protection such as encapsulation or association with cations or clays is known to provide protection from enzymatic attack (Heighton et al, 2008;Hedges et al 2000;Baldock & Skjemstad, 2000). The soil humic acids EHA and LHA have a higher percentage of black carbon or conjugated cyclic carbon (Skjemstad et al, 2002).…”
Section: Discussionmentioning
confidence: 76%